Todos los números el número - Yalta Dorregaray, Adolfo (2018)
The number is an abstract concept that appeared in various geographical points of the planet almost simultaneously but not in a uniform way. Each human group had a particular script to represent them. These numerical dialects were developed until becoming the universal language conformed by the numerical system indoarabic, which is a positional system conformed by ten symbols: 0; 1; 2; 3; 4; 5; 6; 7; 8 and 9. These symbols are called digits in memory of the anthropomorphic basis on which it is assumed to be based (the ten fingers of the hands). The process of counting may have been the primordial application that human beings made of the numbers. Then, as the technology that transformed the surrounding world developed, they used their other basic properties: measuring, ordering, and coding. The numbers that are used to count were called natural numbers but to meet the demands of technological development are insufficient. For this reason, in the course of time, the numbers — currently used — have appeared, that is to say whole, rational, irrational, real and complex. In addition, other real numbers appear, but their use is purely mathematical like the transcendent numbers, algebraic numbers and normal numbers. Since ancient times, natural numbers have also had a ludic function so that, according to certain processes of addition or multiplication, prime numbers, perfect numbers, friend numbers and a long list of numbers with fancy names have been defined. However, it should not be overlooked that the basis for encrypting messages (code encoding function) is based on prime numbers.